2017
DOI: 10.1016/j.ajpath.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

A Dominant Mutation in Rpe65, D477G, Delays Dark Adaptation and Disturbs the Visual Cycle in the Mutant Knock-In Mice

Abstract: RPE65 is an indispensable component of the retinoid visual cycle in vertebrates, through which the visual chromophore 11-cis-retinal (11-cis-RAL) is generated to maintain normal vision. Various blinding conditions in humans, such as Leber congenital amaurosis and retinitis pigmentosa (RP), are attributed to either homozygous or compound heterozygous mutations in RPE65. Herein, we investigated D477G missense mutation, an unprecedented dominant-acting mutation of RPE65 identified in patients with autosomal domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 33 publications
0
19
1
Order By: Relevance
“…The great reduction in Rpe65 mRNA level is only revealed when PCR analysis is done over the region containing the mutation. The importance of the location of the quantitation assays may explain why previous studies have reported comparable levels of mRNA generated in the c.1430G KI mice as that in WT controls (Choi et al., ; Shin et al., ). Similar novel splicing events are also found when the human RPE65 genomic sequence carrying the c.1430G mutation is transcribed in cultured cells, suggesting that the pathogenesis associated with the c.1430G mutation may also be involved in defects in splicing in human.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The great reduction in Rpe65 mRNA level is only revealed when PCR analysis is done over the region containing the mutation. The importance of the location of the quantitation assays may explain why previous studies have reported comparable levels of mRNA generated in the c.1430G KI mice as that in WT controls (Choi et al., ; Shin et al., ). Similar novel splicing events are also found when the human RPE65 genomic sequence carrying the c.1430G mutation is transcribed in cultured cells, suggesting that the pathogenesis associated with the c.1430G mutation may also be involved in defects in splicing in human.…”
Section: Discussionmentioning
confidence: 99%
“…However, when forced‐expressed in cultured cells, RPE65/D477G behaves as a functional RPE65 (Bowne et al., ), with regular subcellular localization, and adequate isomerization activity (Choi et al., ). Moreover, heterozygous RPE65/D477G knock‐in (KI) mice produce sufficient chromophore and have relatively normal retinal structure and function (Choi et al., ; Shin, Moiseyev, Chakraborty, & Ma, ). Taken together, these data do not support the notion that RPE65/D477G acts as a gain‐of‐function missense mutant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This recovery can be monitored using a two-flash protocol (Pepperberg et al, 1996), at the single-cell level and by ERG analysis. Alternate Protocol 1 can be used to monitor photoreceptor deactivation in mice (Chen et al, 1995; Kim et al, 2005; Budzynski et al, 2010; Shin et al, 2017). …”
Section: Basic Protocolmentioning
confidence: 99%
“…Many proteins are involved, and mutations in the genes that encode these proteins have been linked to human retinal disease (Lamb and Pugh, 2004) and these discoveries have also been used to guide the development of relevant mouse models. In these models, dark adaptation recovery is monitored in terms of the growth of the amplitude of the ERG as a function of time following exposure to a bright light that causes a substantial fraction of the rhodopsin molecules to be bleached (e.g., Saari et al, 2001; Kim et al, 2005; Budzynski et al, 2010; Shin et al, 2017). Alternative Protocol 2 can be used to monitor the recovery of the ERG to a previously determined dark-adapted baseline level.…”
Section: Basic Protocolmentioning
confidence: 99%